A ciência das ilhas e os estudos insulares: Breves reflexões sobre o contributo da geografia / The science of islands and the insular studies: Brief point of view about the importance of Geography - Paulo Espínola; Fernanda Cravidão (Sociedade & Natureza)
Throughout the last decades an increase in the interest for the island studies has occurred becoming appealing to researchers from different areas that together have been able to promote this “new” line of research. Considering the international perspective, this text intends to show the main tendencies of research on the island spaces with a particular prominence in the new “science of the islands”. Growing from a recent retrospective analysis about the evolution of the island studies, the main objective of this article is to understand the relation between Geography (as well as geographers) and the islands highlighting the kind of contribute that Geography has been given to this type of territorial analysis. This research is included in a more vast work in the PhD in Geography that we are writing.